Fuzzy Inference System In Predicting Unemployment Levels In Batam City - Nanda Jarti; Sestri Novia Rizki (IJISTECH (International Journal of Information System and Technology), 2020)
Batam city is known as an industrial city in Indonesia; this can be seen from a large number of Indonesians who come to the Riau Islands to work. The company standards in accepting industrial employees can be seen from various aspects, such as age, education, company, opportunities, and job vacancies. Each of these aspects can be used as a decision-making system in predicting unemployment in Batam City. The method in completing this research is using the Sugeno method by taking the highest score and using the operator and. Sugeno's work steps are four. The first is the determination of the input value, the second is the inference engine, the third is the application of the Implementation function, and the fourth is the definition to get the final value—application for determining job vacancies using Matlab software.